Unilateral maxillary swelling: a varied spectrum - Satish, Deepthi; Pratibha, C. B.; Balasubramanya, A. M.; Philip, Sumy (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Diverse disease entities may present with mass in the maxilla and include benign conditions and malignant tumours. A detailed evaluation including preoperative imaging is essential to plan approach to management of isolated maxillary sinus lesions optimally. Methods: We did a retrospective chart review of 14 patients with isolated maxillary swelling and involvement of maxillary sinus who presented to the Department of ENT in a tertiary care hospital over a period of 4 years. A detailed history and examination were done and investigations including contrast enhanced CT scan of the nose and paranasal sinuses was done in all patients. Results: A total of 14 patients were included in this study. 7 were male and 7 were female. The mean age of the patients was 52.6, the age group of patients varied from 6 to 77 years. In our series we had patients with benign lesions like dentigerous cyst, fibro-osseous lesions, mucocele, radicular cyst, aspergilloma, and mucormycosis. Malignant cases included Adenoid cystic carcinoma, Low grade myofibroblastic sarcoma, Diffuse B cell lymphoma and undifferentiated carcinoma. All patients were treated surgically, they underwent a combined endoscopic and Caldwell Luc approach. Conclusions: In patients with unilateral maxillary swelling, a systematic approach to diagnosis with preoperative contrast enhanced CT scan is essential with a high index of suspicion. Trans nasal endoscopic approach with sinus surgery is the preferred approach for these lesions, however, in cases of jaw cysts and odontogenic cysts extending laterally it can be combined with a Caldwel-Luc approach.